Upravljanje gozdnih učnih, turističnih in drugih tematskih poti v Zavodu za gozdove Slovenije - Lesnik, Anton (Gozdarski vestnik, 2008)
The article presents the origin and role of the educational, touristic and other forest paths. It treats the regulations on thematic paths, the responsibility for them and precisely presents the work and tasks of the Slovenia Forest Service in this field.
Keywords: učne poti; gozdne učne poti; zakonodaja